Wireless electronic notice board using GSM / Intan Nabina Azmi & Hazirah Abdul Hisham - Azmi, Intan Nabina; Abdul Hisham, Hazirah (2015)
Nowadays, persons with high critical thinking, which is the genius that inventedseveral of things for upgrade our living style, will try to find way to improve everything around us for more efficient. For examples, mobile phone, computer and Global Positioning System (GPS). Few years ago, these three technologies are in separated but with the innovation and the wide knowledge about technologies we can just pay for the expensive price for one smart phone that content the ability of these three gadgets. Notice boards are one of the widely used ones ranging from primary schools to major organizations to convey messages at large. However, sticking various notices in every single day is a difficult process with a lot of energy. To stick the notices at each single board is required more than one person for more efficient. Besides, a lot of paper is been used and which is later wasted by the organizations. Furthermore, the notices were stick overlapped with the other notice and this may causes people and community missed about the information about the nearer event. This situation shows that the notice board does not operate properly. Thus, the idea to design and build 'Wireless Electronic Notice Board using GSM' is to smooth the operation of the notice board. As a result, people and community will get the news and update without confusing.